Etapy nauchno-issledovatel'skoi deyatel'nosti gosudarstvennoi akademii fizicheskoi kul'tury 1969 - 1999 - Yakobashvili, V. A. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
On the 30 years of history, work and development of the Kuban State Academy of Physical Culture and Sports 1969 - 1999.